Meningkatkan Kemampuan Bahasa Ekpresif (Berbicara) Anak Usia 5-6 Tahun melalui Metode Bercerita dengan Media Wayang Kartun di TK Anak Sholeh Muslimat NU Tuban - Nurul Fitriani (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2022)
This study aims to improve the expressive language skills of TK B children of Sholeh Muslimat NU Tuban aged 5-6 years through the storytelling method using cartoon puppet media. This type of research is classroom action research (CAR) which is carried out in three cycles and each cycle has 2 meetings in each cycle. The subjects of this study were 12 children in the group As Salam Kindergarten B Children of Sholeh Muslimat NU Tuban. The object of the research is the expressive language ability of children through the storytelling method using the puppet media. Data collection techniques using observation, interviews and documentation. The technical analysis of the data used is descriptive quantitative and descriptive qualitative. The indicator of success in this study is if the average expressive language ability of children through the storytelling method using the puppet media has reached the very well developed criteria (BSB) which is 75%. The results of this study indicate that there is an increase in children's expressive language skills through storytelling media with cartoon puppets at Soleh Muslimat NU Tuban Children's Kindergarten. This is evidenced by the increase in the average expressive language ability of children in the pre-action by 35.4167%, increasing to 41.666% in the first cycle of action, then increasing again to 56.25% in the second cycle of action and reaching 78.75% on the action of cycle III.